D‐glucose weighted chemical exchange saturation transfer (glucoCEST)‐based dynamic glucose enhanced (DGE) MRI at 3T: early experience in healthy volunteers and brain tumor patients. Issue 1 (24th December 2019) - Xu, Xiang; Sehgal, Akansha Ashvani; Yadav, Nirbhay N.; Laterra, John; Blair, Lindsay; Blakeley, Jaishri; Seidemo, Anina; Coughlin, Jennifer M.; Pomper, Martin G.; Knutsson, Linda; van Zijl, Peter C. M.
Abstract : Purpose: Dynamic glucose enhanced (DGE) MRI has shown potential for imaging glucose delivery and blood–brain barrier permeability at fields of 7T and higher. Here, we evaluated issues involved with translating d ‐glucose weighted chemical exchange saturation transfer (glucoCEST) experiments to the clinical field strength of 3T. Methods: Exchange rates of the different hydroxyl proton pools and the field‐dependent T 2 relaxivity of water in d ‐glucose solution were used to simulate the water saturation spectra (Z‐spectra) and DGE signal differences as a function of static field strength B 0, radiofrequency field strength B 1, and saturation time tsat . Multislice DGE experiments were performed at 3T on 5 healthy volunteers and 3 glioma patients. Results: Simulations showed that DGE signal decreases with B 0, because of decreased contributions of glucoCEST and transverse relaxivity, as well as coalescence of the hydroxyl and water proton signals in the Z‐spectrum. At 3T, because of this coalescence and increased interference of direct water saturation and magnetization transfer contrast, the DGE effect can be assessed over a broad range of saturation frequencies. Multislice DGE experiments were performed in vivo using a B 1 of 1.6 µT and a tsat of 1 second, leading to a small glucoCEST DGE effect at an offset frequency of 2 ppm from the water resonance. Motion correction was essential to detect DGE effects reliably. Conclusion: Multislice glucoCEST‐based DGE experiments can be performed at 3T with sufficient temporal resolution. However, the effects are small and prone to motion influence. Therefore, motion correction should be used when performing DGE experiments at clinical field strengths.